Prophylaxis and therapy of viral infections in pediatric patients treated for malignancy - Anna Pegoraro; Maria Licciardello; Simone Cesaro (MDPI AG, 2011)
Infections are still an important cause of mortality and morbidity in pediatric cancer patients. Most of the febrile episodes in immunocompromised patients are classified as a fever of unknown origin (FUO) while bacteria are the more frequent causes of documented infections. Viral infections are also feared during chemotherapy but less data are available on their incidence and morbidity. We reviewed the literature on incidence, morbidity, and mortality of viral infections in children undergoing chemotherapy and discussed the evidence concerning the prophylaxis and the therapy.